Comparative analysis of the implementation performance using selected scripting languages in the Godot game engine - Sebastian Alchimowicz; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
This article describes a comparative analysis of the implementation performance of selected scripting languages on the Godot game engine. In order to analyze the implementation of scripting languages, research scenarios were designed in which the scripts were written in a similar way to facilitate the analysis of the performance of their implementation. The study took into account parameters such as the execution time of a given script, processor time and the amount of RAM used. Based on the results obtained, averages were determined and presented in charts to facilitate their interpretation. The conducted research allowed for a comparative analysis between scripting languages. The analysis showed that each language is better suited for different types of projects, with GDScript being better for smaller projects and C# for more complex projects.